Kinerja dan Efisiensi Rantai Pasok Biji Kakao di Kabupaten Pasaman, Sumatera Barat - Herawati Herawati; Amzul Rifin; Netti Tinaprilla (Jurnal Tanaman Industri dan Penyegar, 2015)
Production and marketing area of cocoa in Pasaman is still prospective. However, it faced some problems, such as low price in farmers level, distortion of market information and fluctuative price. Thus, the effective marketing is needed in cocoa beans supply chain. The objective of this study was to analyze the performance of cocoa beans marketing in West Sumatra. The study used primary data which is obtained directly through survey using 64 respondents in Pasaman, West Sumatra from October to November 2014. The method used to analyze cocoa beans supply chain is Food Supply Chain Network (FSCN) approach and descriptive analysis. Marketing performance of cocoa beans was measured by marketing margins, farmer's share, and the ratio of benefits to cost criteria. The results showed that there were six marketing channels of cocoa beans. Marketing agencies involved in this channel are farmer as producer of cocoa beans, farmer trader, village traders, district traders, wholesalers, and exporters. Based on the marketing efficiency analysis, the first channel is more efficient than the others. Marketing margin of channel 1 is 16.1% which is the lowest margin value. Meanwhile, the farmer's share in this channel is 83.9% and the ratio of benefits to costs distribution are relatively spread evenly with total ratio of benefits to costs is 2.4.